The Role of Professional Competencies in Developing a Culture of Safety in the Workplace - Abikenova, Sholpan K.; Oshakbayeva, Zhuldyz O.; Bekmagambetov, Alimzhan B.; Sarybayeva, Inara E. (European Journal of Sustainable Development, 2023)
The paper considers the concept of occupational competencies as an integral part of building a culture of occupational safety in the organization. The paper provides examples of competencies that employees need to effectively perform their job safety responsibilities. It also discusses professional education and training issues related to the development of occupational safety competencies. It is believed that the development of occupational health and safety competencies not only influences the design of appropriate and safe working conditions, but also reduces the risk of occupational accidents and diseases. There are two types of occupational competencies: general and vocational. General occupational competencies are required for effective occupational activities to ensure safe work, regardless of the sector. The sectoral nature of occupational health and safety is reflected in the availability of specific occupational competencies. The article discusses various methods and approaches for building a new national model for professional skills development. The model is based on the introduction of a risk-based approach in Kazakhstan. Occupational risk assessment is considered as the basis for designing training programs and acquiring the occupational competencies needed for comprehensive protection against risks. The development of a culture of occupational safety and professional competencies is a key factor in the sustainable development of the company and the improvement of the quality of life of its employees. Keywords: safe work, risk-oriented approach, professional competencies, industrial accident, training programs.